1981
DOI: 10.2503/jjshs.50.31
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cytokinin and Abscisic Acid in the Maturing of Strawberry Fruits

Abstract: SummaryThe changes of the activity of growth inhibitors in the latter half of the development of strawberry fruits and the interaction of cytokinin and growth inhibitors on fruit development were investigated.1. Fruits grown at day/night temperature of 30°C/25°C matured earlier than those at 20°C/17°C. The activity of growth inhibitors in the fruits increased with their maturing, and inhibitor activity in the fruits grown at high temperature appeared earlier than that at low temperature.In chromatography of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…These results demonstrated that TRV-mediated VIGS is a viable strategy to silence gene expression in strawberry fruit. There are several reports suggesting that strawberry fruit ripening may be promoted by ABA (Kano and Asahira, 1981;Manning, 1994;Perkins-Veazie, 1995;Jiang and Joyce, 2003). To confirm this, we first quantified ABA levels in the receptacles of Fugilia strawberry fruit and detected an increase during development (Fig.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that TRV-mediated VIGS is a viable strategy to silence gene expression in strawberry fruit. There are several reports suggesting that strawberry fruit ripening may be promoted by ABA (Kano and Asahira, 1981;Manning, 1994;Perkins-Veazie, 1995;Jiang and Joyce, 2003). To confirm this, we first quantified ABA levels in the receptacles of Fugilia strawberry fruit and detected an increase during development (Fig.…”
Section: )mentioning
confidence: 99%
“…It has been hypothesized that the ABA-auxin ratio could be part of the signal that triggers fruit ripening (Archbold and Dennis, 1984;Perkins-Veazie, 1995). Auxin stimulates receptacle expansion during early fruit development and later inhibits fruit ripening (Given et al, 1988), whereas exogenous ABA markedly promotes fruit maturation (Kano and Asahira, 1981;Manning, 1994;Perkins-Veazie, 1995;Jiang and Joyce, 2003). This model was supported by studies of another nonclimacteric fruit, the grape berry (Coombe, 1992;Davies et al, 1997;Giovannoni, 2001;Rodrigo et al, 2003;Yu et al, 2006).…”
Section: Aba Is a Central Positive Regulator Of Strawberry Fruit Ripmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, numerous studies demonstrate the antagonistic effects of cytokinin and ABA in plant development (Das et al. , 1976; Kano and Asahira, 1981; Blackman and Davies, 1983; Christianson, 2000; Tanaka et al. , 2006; Polanská et al.…”
Section: Introductionmentioning
confidence: 99%
“…ABA, as the important phytohormone, besides the key roles on plant growth and responses to environmental stresses (Leung and Giraudat, 1998;Finkelstein et al, 2002;Himmelbach et al, 2003;Hirayama and Shinozaki, 2007) was also involved in the ripening of climacteric (Chernys and Zeevaart, 2007;Zhang et al, 2009a) and non-climacteric fruit (Rodrigo et al, 2003;Davies et al, 1997;Zhang et al, 2009b), including strawberry fruit (Kano and Asahira, 1981;Manning 1994;Jiang and Joyce, 2003;Jia et al, 2011). In Arabidopsis, PYR1/PYL1-PP2C-SnRK2 is one of the core signaling transduction networks of ABA, in which ABA could promote the interaction of PYR1/PYL1 and PP2C, repress PP2C and activate SnRK2, then transmit the ABA signals Ma et al, 2009;Park et al, 2009).…”
Section: Discussionmentioning
confidence: 99%